Er(r)rgo... - Kalaga, Wojciech (Er(r)go. Teoria - Literatura - Kultura, 2011)
Er(r)go …, on English studies. And so we submerge into our own spring—since Er(r)go emerged from English studies—and then we follow the arms, the tributaries, the tides. Thus the substantiation of the intellectual mood of the times of the early onset of cultural studies; on the one hand, once a forbidden fruit, on the other, anxieties and fears: it could mean the loss of cultural identity and identity of literary studies; could mean dangerous Marxism, could mean losing aesthetic values and diffusion in egalitarianism. And a related problem: what is the role of English philologists—professionals in promoting foreign culture and foreign language—towards linguistic identity of their nation? Are they sinking the national ship (that’s Sienkiewicz) pumping in linguistic contamination instead of pumping it out, or are they helping the ship to stay afloat on the stormy seas of change? Thus, the ambivalent myth of the English philologist. The English philologist as Robinson Crusoe on an island overgrown with different contexts, Polish and not Polish. And, of course, the problems of translation. The translator as the third element—the mediator between two realities, which do not yield to mediation; subjectivity in translation and the translator’s leap of faith. Desubjectification and the translation industry; a mass fraud. What is there to read, if fools and rogues create reading lists? Thus the fundamental question of canon: equality or elitism? The canon as the foundation and the emanation of identify. Thus away with Dead White European Males! But will the Zulu give us Tolstoy? At least there remains Marquise de Sade’s pornology, but apart from that “nothing, an empty space of the impossibility of identification.” Humanist education as possible salvation? But of what kind? Right-winged, or the search for the only truth, or left-winged, the shaping of intellectual independence? And here the English philologist calls upon Rorty and chooses a compromise, albeit not without hesitations, tensions and polemics. English as Latin of today? The present issue was prepared under the supervision of Leszek Drong